2019
DOI: 10.1016/j.jcma.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Nebulized salbutamol diminish the blood glucose fluctuation in the treatment of non-oliguric hyperkalemia of premature infants

Abstract: Salbutamol nebulization is not only as effective as glucose-insulin infusion for treating non-oliguric hyperkalemia in premature infants but can avoid potential side effects such as vigorous blood glucose fluctuations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A clinical trial in healthy individuals demonstrated that receiving 10 mg nebulized albuterol decreased the potassium level by 0.5 mmol/L, which was not observed in the placebo group [ 47 ]. Nebulization with 200 μg/mL albuterol is not only as effective as 10–15 mg glucose and 1 unit of insulin infusion but can avoid vigorous blood glucose fluctuations [ 48 ]. However, the common adverse reactions of beta-2 agonists include anxiety, tachycardia, palpitations, headache, and musculoskeletal tremors [ 49 , 50 ].…”
Section: Recommendations Of Treatment For Hyperkalemiamentioning
confidence: 99%
“…A clinical trial in healthy individuals demonstrated that receiving 10 mg nebulized albuterol decreased the potassium level by 0.5 mmol/L, which was not observed in the placebo group [ 47 ]. Nebulization with 200 μg/mL albuterol is not only as effective as 10–15 mg glucose and 1 unit of insulin infusion but can avoid vigorous blood glucose fluctuations [ 48 ]. However, the common adverse reactions of beta-2 agonists include anxiety, tachycardia, palpitations, headache, and musculoskeletal tremors [ 49 , 50 ].…”
Section: Recommendations Of Treatment For Hyperkalemiamentioning
confidence: 99%
“…Potassium-containing intravenous fluids should be avoided in infants with AKI. A study of 40 preterm infants (<36 weeks) suggested the use of nebulised salbutamol may be as effective as insulin/dextrose in infants with non-oliguric hyperkalaemia with less impact on blood glucose ( 108 ).…”
Section: Assessment and Managementmentioning
confidence: 99%
“…The vibrating mesh nebulizer results in superior lung deposition of the drug, most likely from smaller residual volume and low operational gas flows ( Table 3 ). 43 …”
Section: Albuterol (Salbutamol)mentioning
confidence: 99%